Corn & Arak (Local Alcohol) as an Alternative to Bread & Wine in the Catholic Ritual of the Eucharist (A Deconstructive Analysis of the Novel “Lembata”) - Orong, Yohanes (Center for Research and Development of Religious Literature and Heritage, 2020)
The purpose of this article is to analyse deconstructively an idea expressed in the novel, “Lembata”, by F. Rahardi. The novel takes its name from an island in the Province of Nusa Tenggara Timur, in Eastern Indonesia. The majority of the people there are Catholic. A priest, Pedro, is given a task there by his bishop. In Lembata, he struggles with the basic problem faced by the people, poverty. Of course that poverty is a complex matter. Facing this, he is concerned by the need to import altar bread and grape wine for use in the Eucharist. He sees this as being an example of the Catholic Church supporting capitalism, which he identifies as the root cause of poverty. Pedro takes a controversial stand. He takes local foods, corn and arak, and uses these in the ritual of the Eucharist, instead of imported bread and wine. Written in a deconstructive way, the novel has elements that have relevant values relating to the way injustice can be perpetrated under the guise of promoting religious piety. As well as raising the question about the possibility of using alternative material to what is the norm in a religious ritual, the novel,“Lembata”, also speaks about the concept of deconstruction and the attitude of the Catholic Church to poverty.